Analisis Pengaruh Limbah Keramik Sebagai Substitusi Semen Terhadap Inovasi Dinding Partisi Kalsiboard - Ivander Satria Sapulette; Adventus Adventus; H Hartono; Shifa Fauziyah (Jurnal Sipil dan Arsitektur, 2024)
The number of infrastructure developments in Indonesia that continues to increase has both positive and negative impacts. One of the negative impacts that arise is the production of construction waste. Along with the increasing number of construction projects, it will also affect the increase in the amount of construction waste produced. Based on data, around 100 million tons of ceramics are produced annually worldwide, and approximately 15% to 30% becomes unused waste. Based on this, the use of ceramic waste as a substitute for making partition walls can be used as a solution to reduce waste in Indonesia. This study aims to determine the effect of using ceramic waste on the partition characteristics produced through dencity, bending strength, and water absorption tests. The research process was carried out using experimental methods in the laboratory with several percentage variations and substitution of ceramic waste against partition walls. This test is done by comparing several partitions on the market (gypsum, kalsiboard, and GRC). Through the test results, it is hoped that this partition board innovation can provide solutions and existing partition problems so that it can reduce problems with construction waste.